Does prudential capital reduce bank risk-taking? Empirical evidence from the Indonesian banks industry - Salim, Agus; Suripto, Suripto (Universitas Muhammadiyah Yogyakarta, 2023)
The implementation of macroprudential supervision, significantly tighter capital regulation in developing economies, has recently been debated, which focuses on reducing bank risk-taking and promoting financial stability in the banking sector. Our study investigates the impact of prudential capital on commercial bank risk-taking in Indonesia. We employed a GMM system approach to analyze bank and macro level data from 2004 to 2019. Our result confirms that appropriate capital regulations for reducing bank risk-taking are heterogeneous. Traditional capital ratios decrease bank risk-taking. However, the risk-based capital ratio shows an unexpected affirmative effect. Implementing macroprudential policy instruments of capital buffer effectively manages bank risk, and so does the regulatory capital pressure variable. The results are intimate for guiding commercial banks' risk management and capital effectiveness.